The Potential Use of Antibiotics Against Helicobacter pylori Infection: Biopharmaceutical Implications - Miri, Amir Hossein; Kamankesh, Mojtaba; Llopis-Lorente, Antoni; Liu, Chenguang; Wacker, Matthias G.; Haririan, Ismaeil; Asadzadeh Aghdaei, Hamid; Hamblin, Michael R.; Yadegar, Abbas; Rad-Malekshahi, Mazda; Zali, Mohammad Reza (Frontiers in Pharmacology, 2022)
Helicobacter pylori is a notorious, recalcitrant and silent germ, which can cause a variety of debilitating stomach diseases, including gastric and duodenal ulcers and gastric cancer. This microbe predominantly colonizes the mucosal layer of the human stomach and survives in the inhospitable gastric microenvironment, by adapting to this hostile milieu. In this review, we first discuss H. pylori colonization and invasion. Thereafter, we provide a survey of current curative options based on polypharmacy, looking at pharmacokinetics, pharmacodynamics and pharmaceutical microbiology concepts, in the battle against H. pylori infection.